STRATEGIC PLANNING IN ACHIEVING OPTIMAL QUALITY OF EDUCATION WITH SCHOOL BASED MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Nomin, Nomin; Resky, Muhammad; Lusiana, Lusiana (JURNAL EDUCATION AND DEVELOPMENT, 2025)
School Based Management (SBM) has been implemented in Indonesia as an effort to improve the quality of education through the granting of autonomy to schools. However, its implementation still faces significant obstacles, such as the gap between expectations and reality on the ground, as well as the low involvement of the school component in decisionmaking. This study aims to evaluate the role of leadership, strategic planning, and management of Human Resources (HR) in supporting the effectiveness of SBM. The research method used is Systematic Literature Review (SLR) by analyzing various scientific articles related to SBM that are relevant in the last 10 years. The results showed that transformative Principal Leadership, Strategic Planning based on SWOT analysis, and optimal human resources management through teacher competency development are important factors in achieving the success of SBM. The implications of this study emphasize the need for education policies that support leadership training, increased community involvement, and external collaboration to accelerate the achievement of equitable education quality in Indonesia. The importance of this study to highlight transformative leadership, strategic planning, and optimal HR management for the future, this study shows how to improve the quality of education equally.